Analisis Promosi Penjualan Terhadap Keputusan Pembelian Di Transmart Tuparev Karawang - Winda Apriani; Syifa Pramudita Fadilla (Jurnal Bintang Manajemen, 2023)
Sales promotion is one element of marketing communication that influences consumer purchasing decisions. The purpose of the research conducted was to find out whether sales promotions carried out by Transmart Tuparev Karawang affect purchasing decisions at Transmart Tuparev Karawang. The independent variable used in this study is Sales Promotion (x) while the dependent variable is Purchase Decision (y). The research method used in this research is quantitative research using a simple linear regression method. The population studied was Transmaart Tuparev Karawang visitors in April 2023 with a total of 8648 visitors. Samples were taken as many as 99 respondents with a sampling technique using the Slovin formula and data collection using questionnaires, observation, interviews, and literature study. The results of this study are that there is an effect of sales promotion on purchasing decisions at Transmart Tuparev Karawang of 46.50%, namely the effect of sales promotion on purchasing decisions is included in the medium category and the remaining 53.50% is influenced by other variables not examined by the author.